Overweight effects on metabolic rate, time perception, diseases, aging, and lifespan: A systematic review with meta-regression analysis - Kuat Oshakbayev; Aigul Durmanova; Altay Nabiyev; Antonio Sarria-Santamera; Alisher Idrissov; Gulnara Bedelbayeva; Abduzhappar Gaipov; Ayan Mitra; Meruyert Gazaliyeva; Bibazhar Dukenbayeva; Gani Kuttymuratov (Translational Medicine of Aging, 2025)
Background: The hypothesis that metabolic rate (MR) is inversely correlated with lifespan has long been debating. Another area of controversy is the relationship between MR and time-flow perception (TFP), and aging. Objectives: to study the impact of overweight and excess food intake on MR, TFP, chronic diseases, aging, lifespan. Methods: Design: a systematic review. Settings: Web of Science, Scopus, Science Direct, Kopernio, PubMed, and Mendeley were searched for articles published for 44 years (1979–2022). The study bases on a systematic literature review of 3612 articles published worldwide. Results: In total, 107 full-text articles were assessed for eligibility. Overweight/overeating accelerates MR, leading to a hyper-metabolic mode of the body. MR and lifespan are inversely correlated. TFP depends on MR; accelerated MR provides TFP deceleration.Every person has an individual ability to gain weight up to ‘maximum bodyweight’, which indicates the individual potential energy for weight gain. Overweight excessively consumes the body's ‘vital energy’, and devours the body potential energy. Weight loss creates ‘body potential power to weight gain’ that increases physical/mental activity, recovers from disease, or weight regain. The body should consume fewer calories due the decline in MR with age. Conclusions: Our findings support that overweight and overeating increase in MR, which delays time-flow perception, accelerates aging, and limits lifespan. Metabolic intoxication should be managed during weight loss. Trial registration: ClinicalTrials.gov NCT06410352 (05/08/2024): https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000EG8K&selectaction=Edit&uid=U0006MBT&ts=56&cx=-vph5l9.